Optimized Carbonization and Kinetic Analysis of Palm Kernel Shell Porous Carbon for Heavy Metal Adsorption - Hafizah, Mas Ayu Elita; Manaf, Azwar; Valency, Tiara; Andreas, Andreas; Manawan, Maykel (Universitas Gadjah Mada, 2025)
This study explores the use of porous carbon derived from palm kernel shells to adsorb lead ions (Pb2+) from water. Porous carbon was produced by carbonizing palm kernel shells at different temperatures (400, 600, and 800 °C) and was evaluated for its effectiveness in a lead chloride (PbCl2) solution. The best adsorption rate, reducing Pb2+ concentration by 27.5%, was observed by carbonized material at 800 °C with a 3 h contact time. Kinetic analysis suggested that the process followed a pseudo-second-order model, indicating that chemical adsorption was the dominant mechanism. The adsorption data were best described by the Freundlich isotherm, implying multilayer adsorption on an uneven surface. These findings highlight the efficient and low-cost potential of palm kernel shell-based porous carbon for removing heavy metals from wastewater. Palm kernel shell-derived porous carbon has proven to be a sustainable, cost-effective, and practical solution for mitigating Pb2+ contamination, positioning it as a promising candidate for environmentally friendly water treatment applications.